The phytoestrogen genistein affects zebrafish development through two different pathways. - Sana Sassi-Messai; Yann Gibert; Laure Bernard; Shin-Ichi Nishio; Karine F Ferri Lagneau; José Molina; Monika Andersson-Lendahl; Gérard Benoit; Patrick Balaguer; Vincent Laudet (PLoS ONE, 2009)
BACKGROUND: Endocrine disrupting chemicals are widely distributed in the environment and derive from many different human activities or can also be natural products synthesized by plants or microorganisms. The phytoestrogen, genistein (4', 5, 7-trihydroxy-isoflavone), is a naturally occurring compound found in soy products. Genistein has been the subject of numerous studies because of its known estrogenic activity. METHODOLOGY/PRINCIPAL FINDINGS: We report that genistein exposure of zebrafish embryos induces apoptosis, mainly in the hindbrain and the anterior spinal cord. Timing experiments demonstrate that apoptosis is induced during a precise developmental window. Since adding ICI 182,780, an ER antagonist, does not rescue the genistein-induced apoptosis and since there is no synergistic effect between genistein and estradiol, we conclude that this apoptotic effect elicited by genistein is estrogen-receptors independent. However, we show in vitro, that genistein binds and activates the three zebrafish estrogen receptors ERalpha, ERbeta-A and ERbeta-B. Furthermore using transgenic ERE-Luciferase fish we show that genistein is able to activate the estrogen pathway in vivo during larval stages. Finally we show that genistein is able to induce ectopic expression of the aromatase-B gene in an ER-dependent manner in the anterior brain in pattern highly similar to the one resulting from estrogen treatment at low concentration. CONCLUSION/SIGNIFICANCE: TAKEN TOGETHER THESE RESULTS INDICATE THAT GENISTEIN ACTS THROUGH AT LEAST TWO DIFFERENT PATHWAYS IN ZEBRAFISH EMBRYOS: (i) it induces apoptosis in an ER-independent manner and (ii) it regulates aromatase-B expression in the brain in an ER-dependent manner. Our results thus highlight the multiplicity of possible actions of phytoestrogens, such as genistein. This suggests that the use of standardized endpoints to study the effect of a given compound, even when this compound has well known targets, may carry the risk of overlooking interesting effects of this compound.